Managing wilding pines in the Cape Floristic Region, South Africa: Progress and prospects - Grant Martin; Kim Canavan; Gerald Chikowore; Richard Bugan; Willem De Lange; Ben du Toit; Graham Harding; Ronald Heath; Martin Hill; Brett P. Hurley; Philip Ivey; Debbie Muir; et al. (South African Journal of Botany, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Opportunities and challenges for use of minipigs in nonclinical pharmaceutical development: Results of a follow-up IQ DruSafe survey - David O. Clarke; Kaushik Datta; Kevin French; Michael W. Leach; Drew Olaharski; Susanne Mohr; Devon Strein; Jeanine Bussiere; Bianca Feyen; Beatrice E. Gauthier; Michael Graziano; Joanna Harding; et al. (Regulatory Toxicology and Pharmacology, 2024)

Using a GFP-labeled Stagonospora nodorum strain as a DNA extraction efficiency standard in plant disease diagnosis - Heting Fu; Yalong Yang; Kher Zahr; Shiming Xue; Junye Jiang; Michael W. Harding; David Feindel; Jie Feng (Crop Protection, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

Plenodomus tracheiphilus, but not Dothiorella ulmi, causes wilt disease on elm trees in Alberta, Canada - Yalong Yang; Heting Fu; Kher Zahr; Shiming Xue; James Calpas; Krista Demilliano; Michael W. Harding; David Feindel; Jie Feng (European Journal of Plant Pathology, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Chemical and Water-Isotope Composition Unravels the Source and Evolution of the Kittilä Underground Mine Water, Kiistala, Finland - V. Milesi; J. Declercq; W. Harding; T. Jarman; O. Baas; J. Saukkoriipi; A. van Wageningen; R. Bowell (Mine Water and the Environment, 2023)

Discovery of three cycloviruses in fecal samples from silver-haired bats (Lasionycteris noctivagans) in Arizona (USA) - Ciara Harding; Brendan B. Larsen; Sophie Gryseels; Hans W. Otto; Crystal Suazo; Simona Kraberger; Nathan S. Upham; Michael Worobey; Koenraad Van Doorslaer; Arvind Varsani (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Plasmodiophora brassicae infection threshold—how many resting spores are required for generating clubroot galls on canola (Brassica napus) - Kher Zahr; Yalong Yang; Alian Sarkes; Snezana Dijanovic; Heting Fu; Michael W. Harding; David Feindel; Jie Feng (Journal of Plant Diseases and Protection, 2022)

Origin and expansion of the world’s most widespread pinniped: Range‐wide population genomics of the harbour seal ( Phoca vitulina ) - Xiaodong Liu; Suzanne Rønhøj Schjøtt; Sandra M. Granquist; Aqqalu Rosing‐Asvid; Rune Dietz; Jonas Teilmann; Anders Galatius; Kristina Cammen; Greg O’Corry‐Crowe; Karin Harding; Tero Härkönen; Ailsa Hall; et al. (Molecular Ecology, 2022)
The harbour seal ( Phoca vitulina ) is the most widely distributed pinniped, occupying a wide variety of habitats and climatic zones across the Northern Hemisphere. Intriguingly, the harbour seal is also one of the most philopatric seals, raising questions as to how it colonized its current range. To shed light on the origin, remarkable range expansion, population structure and genetic diversity of this species, we used genotyping‐by‐sequencing to analyse ~13,500 biallelic single nucleotide polymorphisms from 286 individuals sampled from 22 localities across the species’ range. Our results point to a Northeast Pacific origin of the harbour seal, colonization of the North Atlantic via the Canadian Arctic, and subsequent stepping‐stone range expansions across the North Atlantic from North America to Europe, accompanied by a successive loss of genetic diversity. Our analyses further revealed a deep divergence between modern North Pacific and North Atlantic harbour seals, with finer‐scale genetic structure at regional and local scales consistent with strong philopatry. The study provides new insights into the harbour seal's remarkable ability to colonize and adapt to a wide range of habitats. Furthermore, it has implications for current harbour seal subspecies delineations and highlights the need for international and national red lists and management plans to ensure the protection of genetically and demographically isolated populations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

First report of Triticum mosaic virus infecting wheat in Canada - Harvinder Bennypaul; Ismail Abdullahi; Reem Aboukhaddour; Michael W. Harding (Journal of Plant Pathology, 2021)

Impact of DNA extraction efficiency on the sensitivity of PCR-based plant disease diagnosis and pathogen quantification - Yalong Yang; Qixing Zhou; Kher Zahr; Michael W. Harding; David Feindel; Jie Feng (European Journal of Plant Pathology, 2021)

Diversity in the population of Fusarium graminearum isolated from wheat and corn in Alberta, Canada - Hafiz Ahmed; Qixing Zhou; Kher Zahr; Yalong Yang; Heting Fu; Alian Sarkes; Yingli Wang; Krista Zuzak; David Feindel; Greg C. Daniels; Michael W. Harding; Jie Feng (Journal of Plant Diseases and Protection, 2020)

Differences in reported sun protection practices, skin cancer knowledge, and perceived risk for skin cancer between rural and urban high school students - Elizabeth S. Nagelhout; Bridget G. Parsons; Benjamin Haaland; Kenneth P. Tercyak; Kelsey Zaugg; Angela Zhu; Garrett Harding; Jeffrey Yancey; Jakob D. Jensen; Douglas Grossman; David W. Wetter; Yelena P. Wu (Cancer Causes & Control, 2019)

Assessing the availability of life cycle assessments in Austria - A. O. Ladenika; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; Taahira Goga; O. S. MacGregor; Mpho Maepa; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2019)

Invasive Nitrogen-Fixing Plant Amplifies Terrestrial–Aquatic Nutrient Flow and Alters Ecosystem Function - Simon D. Stewart; Megan B. Young; Jon S. Harding; Travis W. Horton (Ecosystems, 2019)

Review: the availability of life-cycle studies in Sweden - Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Taahira Goga; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2019)

Comparative Biology of Cycad Pollen, Seed and Tissue - A Plant Conservation Perspective - J. Nadarajan; E. E. Benson; P. Xaba; K. Harding; A. Lindstrom; J. Donaldson; C. E. Seal; D. Kamoga; E. M. G. Agoo; N. Li; E. King; H. W. Pritchard (The Botanical Review, 2018)

The availability of life-cycle assessment, water footprinting, and carbon footprinting studies in Brazil - Michael O. Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; Taahira Goga; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

A discussion on the availability of life-cycle assessment studies in New Zealand - Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael O. Bodunrin; Nicholas W. Burman; Joel Croft; Taahira Goga; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

Review: life-cycle assessment, water footprinting, and carbon footprinting in Portugal - Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael Oluwatosin Bodunrin; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Review: life cycle assessments in Nigeria, Ghana, and Ivory Coast - Mpho Maepa; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2017)

Dopamine D1 and D3 receptor interactions in cocaine reward and seeking in rats - E. Galaj; W. Harding; R. Ranaldi (Psychopharmacology, 2016)

Comparing total body lipid content of young‐of‐the‐year Steller sea lions among regions of contrasting population trends - Lorrie D. Rea; Brian S. Fadely; Sean D. Farley; Julie P. Avery; Wendy S. Dunlap‐Harding; Vicki K. Stegall; Carrie A. B. Eischens; Tom S. Gelatt; Kenneth W. Pitcher (Marine Mammal Science, 2016)
Steller sea lion ( Eumetopias jubatus ) young‐of‐the‐year ( YOY ) are nutritionally dependent upon their dam through the majority of their first year. Several indices of body condition were measured in YOY 1.5–9 mo of age captured in Southeast Alaska ( n = 122), the Gulf of Alaska ( n = 182), and the Aleutian Islands ( n = 38) to test the hypothesis that nutritional stress impacted the ability of adult female Steller sea lions to adequately nourish their late gestation YOY in the central Aleutian Islands in the early 2000s. Body mass (kg) and percent total body lipid content (% TBL ) increased with age in all three regions of Alaska that were sampled ( P P TBL measured by isotope dilution. The trend for Aleutian Island YOY to have larger body mass and larger body fat reserves are counter to what would be expected if dams were unable to adequately provision their late lactation YOY due to inadequate food availability in the central Aleutian Islands.

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

Designing a sustainable monitoring framework for assessing impacts of climate change at Joshua Tree National Park, USA - Cameron W. Barrows; Josh Hoines; Kathleen D. Fleming; Michael S. Vamstad; Michelle Murphy-Mariscal; Kristen Lalumiere; Mitzi Harding (Biodiversity and Conservation, 2014)

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

The brain renin–angiotensin system: a diversity of functions and implications for CNS diseases - John W. Wright; Joseph W. Harding (Pflügers Archiv - European Journal of Physiology, 2013)

EPG monitoring of the probing behaviour of the common brown leafhopper Orosius orientalis on artificial diet and selected host plants - Piotr Trębicki; W. Fred Tjallingii; Rob M. Harding; Brendan C. Rodoni; Kevin S. Powell (Arthropod-Plant Interactions, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Adverse foraging conditions may impact body mass and survival of a high Arctic seabird - Ann M. A. Harding; Jorg Welcker; Harald Steen; Keith C. Hamer; Alexander S. Kitaysky; Jérôme Fort; Sandra L. Talbot; Leslie A. Cornick; Nina J. Karnovsky; Geir W. Gabrielsen; David Grémillet (Oecologia, 2011)

Living with the enemy: parasites and pathogens of the ladybird Harmonia axyridis - Helen E. Roy; Emma Rhule; Susanne Harding; Lori-Jayne Lawson Handley; Remy L. Poland; Eric W. Riddick; Tove Steenberg (BioControl, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Cryoconservation of South African plant genetic diversity - Patricia Berjak; Paul Bartels; Erica E. Benson; Keith Harding; David J. Mycock; Norman W. Pammenter; Sershen; James Wesley-Smith (In Vitro Cellular & Developmental Biology - Plant, 2011)

Coadministration of intravenous nicotine and oral alcohol in rats - A. D. Lê; Steven Lo; Stephen Harding; Walter Juzytsch; Peter W. Marinelli; Douglas Funk (Psychopharmacology, 2010)

Estuarine Ecosystem Response Captured Using a Synoptic Climatology - David G. Kimmel; W. David Miller; Lawrence W. Harding; Edward D. Houde; Michael R. Roman (Estuaries and Coasts, 2009)

Pleistocene glaciation events shape genetic structure across the range of the American lobster, Homarus americanus - ELLEN L. KENCHINGTON; GARETH C. HARDING; MATHEW W. JONES; PAULO A. PRODÖHL (Molecular Ecology, 2009)
A north/south discontinuity along the northeastern coast of North America in the genetic structure of the American lobster ( Homarus americanus ) was detected using a suite of 13 microsatellite loci assessed using spatial analyses. Population genetic data laid over existing data on physiographic changes and sea‐surface temperatures were used to reconstruct the Pleistocene distribution of this species. A postglacial northern‐edge colonization model best explains the relative genetic homogeneity of the northern region compared to the southern region centred in the Gulf of Maine. Population genetic analyses identified significant structure (range of standardized theta 0–0.02) but no significant evidence for isolation by distance. The novel application of spatial genetic analyses to a marine species allowed us to interpret these results by providing a greater insight into the evolutionary factors responsible for shaping the genetic structure of this species throughout is natural range.

Influence of environmental factors and female size on reproductive output in an invasive temperate marine gastropod Rapana venosa (Muricidae) - Juliana M. Harding; Roger Mann; Catherine W. Kilduff (Marine Biology, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

The CRF1 receptor antagonist antalarmin attenuates yohimbine-induced increases in operant alcohol self-administration and reinstatement of alcohol seeking in rats - Peter W. Marinelli; Douglas Funk; Walter Juzytsch; Stephen Harding; Kenner C. Rice; Yavin Shaham; A. D. Lê (Psychopharmacology, 2007)

Evaluation of potato production best management practices - Bryan G. Hopkins; Donald A. Horneck; Mark J. Pavek; Brad D. Geary; Nora L. Olsen; Jason W. Ellsworth; George D. Newberry; Jeff S. Miller; Robert E. Thornton; Gale W. Harding (American Journal of Potato Research, 2007)

Effects of dexfenfluramine and 5-HT3 receptor antagonists on stress-induced reinstatement of alcohol seeking in rats - Anh Dzung Lê; Douglas Funk; Stephen Harding; W. Juzytsch; Paul J. Fletcher; Yavin Shaham (Psychopharmacology, 2006)

Anthropogenic and climatic influences on the eutrophication of large estuarine ecosystems - Hans W. Paerl; Lexia M. Valdes; Benjamin L. Peierls; Jason E. Adolf; Lawrence Jr. W. Harding (Limnology and Oceanography, 2006)
We examined the effects of anthropogenic and climatic perturbations on nutrient—phytoplankton interactions and eutrophication in the waters of the largest estuarine systems in the U.S.A., the Chesapeake Bay (CB), Maryland/ Virginia, and the Neuse River Estuary/Pamlico Sound (NRE/PS) system, North Carolina. Both systems have experienced large post‐World War II increases in nitrogen (N) and phosphorus (P) loading, and nutrient reductions have been initiated to alleviate symptoms of eutrophication. However, ecosystem‐level effects of these nutrient reductions are strongly affected by hydrologic variability, including severe droughts and a recent increase in Atlantic hurricane activity. Phytoplankton community responses to these hydrologic perturbations, including storm surges and floods, were examined and when possible, compared for these systems. In both systems, the resulting variability in water residence time strongly influenced seasonal and longer‐term patterns of phytoplankton biomass and community composition. Fast‐growing diatoms were favored during years of high discharge and short residence time in CB, whereas this effect was not observed during high discharge conditions in the longer residence time NRE/ PS. In the NRE/PS, all phytoplankton groups except summer cyanobacterial populations showed decreased abundance during elevated flow years when compared to low flow years. Although hurricanes affected the CB less frequently than the NRE/PS, they nonetheless influenced floral composition in both systems. Seasonally, hydrologic perturbations, including droughts, floods, and storm‐related deep mixing events, overwhelmed nutrient controls on floral composition. This underscores the difficulty in predicting seasonal and longer‐term phytoplankton production and compositional responses to nutrient input reductions aimed at controlling eutrophication of large estuarine ecosystems.

Effects of unconditioned and conditioned social defeat on alcohol self-administration and reinstatement of alcohol seeking in rats - D. Funk; S. Harding; W. Juzytsch; A. D. Lê (Psychopharmacology, 2005)

k Opioids as potential treatments for stimulant dependence - Thomas E. Prisinzano; Kevin Tidgewell; Wayne W. Harding (The AAPS Journal, 2005)

Phytoplankton production, biomass and community structure following a summer nutrient pulse in Chesapeake Bay - Christina L.J. Yeager; Lawrence W. Harding; Michael E. Mallonee (Aquatic Ecology, 2005)

Role of alpha-2 adrenoceptors in stress-induced reinstatement of alcohol seeking and alcohol self-administration in rats - A. D. L; S. Harding; W. Juzytsch; D. Funk; Y. Shaham (Psychopharmacology, 2005)

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

Petrographic analysis using cathodoluminescence microscopy with simultaneous energy-dispersive X-ray spectroscopy - W. Vortisch; D. Harding; J. Morgan (Mineralogy and Petrology, 2003)

Nicotine increases alcohol self-administration and reinstates alcohol seeking in rats - A. D. Lê; A. Wang; S. Harding; W. Juzytsch; Y. Shaham (Psychopharmacology, 2003)

Ca2+ and the bacterial peroxidases: the cytochrome c peroxidase from Pseudomonas stutzeri - Cristina G. Timóteo; Pedro Tavares; Celia F. Goodhew; Luís C. Duarte; Kornelia Jumel; Francisco M. Gírio; Steven Harding; Graham W. Pettigrew; Isabel Moura (JBIC Journal of Biological Inorganic Chemistry, 2003)

Evaluating Microbial Indicators of Environmental Condition in Oregon Rivers - ALAN T. PENNINGTON; ANNA K. HARDING; CHARLES W. HENDRICKS; HEIDI M. K. CAMPBELL (Environmental Management, 2001)

The Potato Association of America - Steven R. James; Lori Wing; Ronald Knight; Barbara Harrity; Devid H. Lambert; Bud Platt; Al Reeves; Bill Bohl; Lind Sanford; Alexander D. Pavlista; Ed Plissey; Richard Sawyer; et al. (American Journal of Potato Research, 2000)

The role of corticotrophin-releasing factor in stress-induced relapse to alcohol-seeking behavior in rats - A. D. Lê; S. Harding; W. Juzytsch; J. Watchus; U. Shalev; Y. Shaham (Psychopharmacology, 2000)

Koala Conservation Policy Process: Appraisal and Recommendations - Tim W. Clark; Nicole Mazur; Steven J. Cork; Steve Dovers; Ronnie Harding (Conservation Biology, 2000)
Australia's koalas are a global treasure, yet there is growing concern that present policy may not adequately conserve viable, wild populations in abundant habitats. Problems in the content and particularly the process of policy making for koala conservation include integrating reliable knowledge and diverse perspectives. We reviewed the overall decision process involved in developing Koala conservation policy, including the functions of intelligence, promotion, prescription, invocation, application, appraisal, and termination. To date, intelligence ( planning ) has lacked social science data, and promotion (open debate) has been confrontational. Koala policy has been unclear about prescription (setting rules) and lacks specificity about needed standards, penalties for violating standards, and making resources available. Invocation and application (implementation) have been differentially successful. Appraisal has been adversarial and incomplete, and termination of weak practices has been difficult. We suggest implementation of procedural standards such as timeliness, comprehensiveness, and rationality for a better koala decision process. The 1998 National Koala Conservation Strategy and various state policies can be upgraded to meet these standards. Opportunities exist to improve koala management policy in all seven functions. We recommend a three‐part strategy: (1) identify, describe, and appraise successful conservation efforts to find the best practices, (2) disseminate success stories, and (3) open up new opportunities for improvement in all aspects of koala conservation.

Interactive image processing system for assessment of cell movement - A. Hoppe; D. Wertheim; W. G. Jiang; R. Williams; K. Harding (Medical & Biological Engineering & Computing, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Alteration of the quaternary structure of glutamate dehydrogenase from Clostridium symbiosum by a single mutation distant from the subunit interfaces - Jonathan L. E. Dean; H. Cölfen; Stephen E. Harding; David W. Rice; P. C. Engel (European Biophysics Journal, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Handwipe sampling and analysis procedure for the measurement of dermal contact with pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos; R. G. Lewis (Archives of Environmental Contamination and Toxicology, 1996)

Handwipe Sampling and Analysis Procedure for the Measurement of Dermal Contact with Pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos (Archives of Environmental Contamination and Toxicology, 1996)

A monoclonal antibody which recognizes cell surface antigen and inhibits porcine parvovirus replication - M. J. Harding; T. W. Molitor (Archives of Virology, 1992)

Organochlorine pesticides and polychlorinated biphenyls in the Arctic Ocean food web - B. T. Hargrave; G. C. Harding; W. P. Vass; P. E. Erickson; B. R. Fowler; V. Scott (Archives of Environmental Contamination and Toxicology, 1992)

Influence of seed placement on Russet Burbank potato yield and grade - J. L. Halderson; J. C. Ojala; G. W. Harding; E. V. Musselman (American Journal of Potato Research, 1992)

Porcine parvovirus: replication in and inhibition of selected cellular functions of swine alveolar macrophages and peripheral blood lymphocytes - M. J. Harding; T. W. Molitor (Archives of Virology, 1988)